The acromegaly lipodystrophy - Freda, Pamela U. (Frontiers in Endocrinology, 2022)
GH and IGF-1 are essential to normal growth, metabolism and body composition, but in acromegaly, excesses of these hormones strikingly alter them. In recent years, the use of modern methodologies to assess body composition in patients with acromegaly has revealed novel aspects of the acromegaly phenotype. In particular, acromegaly presents a unique pattern of body composition changes in the setting of insulin resistance that we propose herein be considered an acromegaly-specific lipodystrophy. The lipodystrophy, initiated by a distinctive GH-driven adipose tissue dysregulation that features, in the setting of insulin resistance, reduced visceral adipose tissue (VAT) mass and intra-hepatic lipid (IHL), but lipid redistribution resulting in ectopic lipid deposition in muscle. With recovery of the lipodystrophy, adipose tissue mass, especially that of VAT, and IHL rise, but insulin resistance is lessened. Abnormalities of adipose tissue adipokines may play a role in the disordered adipose tissue metabolism and insulin resistance of the lipodystrophy. The orexigenic hormone ghrelin and peptide Agouti-related peptide (AgRP) may also be affected by active acromegaly as well as variably by acromegaly therapies, which may contribute to the lipodystrophy. Understanding the pathophysiology of the lipodystrophy and how acromegaly therapies differentially reverse its features may be important to optimizing long-term outcome for patients with this disease. This perspective describes evidence in support of this acromegaly lipodystrophy model and its relevance to acromegaly pathophysiology and the treatment of patients with acromegaly.